Healthy diets and reduced land pressure: Towards a double gain for future food systems in Nigeria - Smeets-Kristkova, Zuzana; Achterbosch, Thom; Kuiper, Marijke (MDPI, 2019)
Nigeria is one of the most dynamic economies in Africa. Strong GDP and population growth coupled with urbanization trends place tremendous pressures on natural resources and the food systems that are dependent on them. Understanding the impact of these “mega trends” is important to identify key leverage points for navigating towards improved nutrition and food security in Nigeria. This paper contributes to the Foresight Project of the Food Systems for Healthier Diets which aims to analyse how the food system in Nigeria is expected to transform in the next decades, and to identify the leverage points for making sure that the transformation contributes to balanced consumer diets. For the food systems foresight, a well-established global economy-wide model, MAGNET, is applied that enables to capture the interlinkages among different food industry players in one consistent framework. By linking MAGNET to the GENUS nutritional database, it is further possible to relate the developments occurring on a macro-level with detailed macro and micronutrient consumption. Model projections suggest that a process of intensification of agriculture in combination with land substitution appears critical for the evolution of food and nutrition security, and for shifts towards healthy diets for the population. Intensification results in greater diversity of the production systems, which in turn cascades into positive effects on the diversity in the food supply and better food security outcomes.